The Mediation Of Organizational Citizenship Behavior The Effect Of Organizational Commitment On Work Performance Of Employees In Bawen District, Semarang Regency - Mada Adi Wibowo; Pandi Afandi; Hardi Utomo; Endang Purwanti; Fudji Sri Marati (Return : Study of Management, Economic and Bussines, 2023)
This study aims to examine the Mediation of Organizational CitizenshipBehavior the Effect of Organizational Commitment on Work Performance ofEmployees in Bawen District, Semarang Regency. The population of thisresearch is employees in Bawen District. Where the sample that will be usedas respondents in this study is Bawen District Employees with a total of 31respondents. The sampling technique is saturated sampling. The types of dataused are primary and secondary. Data collection methods are questionnairesand documentation. The analytical technique used is Path Analysis. Theresults of the calculation show that the indirect effect of OrganizationalCommitment on Work Performance through OCB is smaller than the directeffect of Organizational Commitment on Work Performance, so it canguarantee that OCB is not able to become a variable that mediatesOrganizational Commitment to Work Performance. This shows that thetendency of Organizational Commitment to work will not affect the OCB andfrom the OCB obtained, it will not affect the Work Performance applied bythe employees